Personal data protection in E-commerce transaction / Farah Shafinaz Izhar, Affiza Affundi and Mariam Ramli. - Izhar, Farah Shafinaz; Affundi, Affiza; Ramli, Mariam (Faculty of Law, 2005)
Since the development of information technology accelerated further, the issue of protecting personal data in cyberspace is becoming a major concern, with the development of information technology. Electronic commerce transaction has been utilized by business organization to ensure the efficacy of business transaction for consumers. However, as there is no law on the protection of personal data in Malaysia, consumers' personal data may be misused by business organizations conducting ecommerce. Generally, consumers need to resort to using of certain technologies to ensure the protection of their personal data. However, it does not guarantee that their personal data is fully protected, unless the consumers know how to take advantage of it. The main aim of this thesis is to study the importance of protecting personal data and whether the current draft legislation is comprehensive enough to ensure its protection. Apart from that, this study compares between the laws and the international instruments as found in the United States and European Union. These laws will then be analyzed to determine whether or not they can be a model for our propose law. In order to produce this thesis, various sources including legal materials such as statutes, international conventions and instruments, case law, law journals and law reports have been referred to. Interviews have also been conducted with individual and academician that have expertise in this field. We would like to propose there should be a law that will fully protect the consumers1 personal data in order to ensure the healthy development of e-commerce.